-19x+23y=-3

Simple and best practice solution for -19x+23y=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -19x+23y=-3 equation:


Simplifying
-19x + 23y = -3

Solving
-19x + 23y = -3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-23y' to each side of the equation.
-19x + 23y + -23y = -3 + -23y

Combine like terms: 23y + -23y = 0
-19x + 0 = -3 + -23y
-19x = -3 + -23y

Divide each side by '-19'.
x = 0.1578947368 + 1.210526316y

Simplifying
x = 0.1578947368 + 1.210526316y

See similar equations:

| 3x+14x+2=19 | | -4p+15=-15 | | =5(x+3)+3(y+1) | | 5x-3(x-4)=-5+4x+13 | | (x+8)(x-7)=16 | | 0=-16t^2+20t+40 | | -4w-4= | | 99-4s-6s=-9 | | 9=b | | y=xcos(x) | | 2+2=8b | | 2x-5(x-5)=-4+3x+17 | | =2(x+y)+9x+6y | | 42=3(2-6h) | | z+8(z-4)=-4 | | 2x^2-9x-12=0 | | 77-7x=11x+19 | | 6x=24+3x | | B=58b | | 3(m+5)=39 | | S=6-3 | | c-80=36 | | X=38-(-x) | | 3(x+4)-(x+5)=x+4 | | =7+4(x+5) | | f=6q-4 | | -23b=35b | | .23x+.45=8-.32x | | 3x+-7+2x=9 | | 3x-8=5x+3 | | 18x^2-25x=-8 | | 0=-16t^2+60 |

Equations solver categories